2023
DOI: 10.1371/journal.pone.0280956
|View full text |Cite
|
Sign up to set email alerts
|

Digital transition in rural emergency medicine: Impact of job satisfaction and workload on communication and technology acceptance

Abstract: Background Tele-emergency physicians (TEPs) take an increasingly important role in the need-oriented provision of emergency patient care. To improve emergency medicine in rural areas, we set up the project ‘Rural|Rescue’, which uses TEPs to restructure professional rescue services using information and communication technologies (ICTs) in order to reduce the therapy-free interval. Successful implementation of ICTs relies on user acceptance and knowledge sharing behavior. Method We conducted a factorial desig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…The 14 items satisfaction scale had a satisfactory reliability of Cronbach's alpha = 0.78. In other studies the same scale within the PhysicianPlus project (Hasebrook et al, 2016b;Hinkelmann et al, 2017; as well as in another project (Hasebrook et al, 2022) the scale was found to be highly reliable between an Cronbach's Alpha of 0.91 to 0.78 . In this study, items show low intercorrelations (see Supplementary Appendix 5).…”
Section: Satisfaction Scale and Npsmentioning
confidence: 68%
“…The 14 items satisfaction scale had a satisfactory reliability of Cronbach's alpha = 0.78. In other studies the same scale within the PhysicianPlus project (Hasebrook et al, 2016b;Hinkelmann et al, 2017; as well as in another project (Hasebrook et al, 2022) the scale was found to be highly reliable between an Cronbach's Alpha of 0.91 to 0.78 . In this study, items show low intercorrelations (see Supplementary Appendix 5).…”
Section: Satisfaction Scale and Npsmentioning
confidence: 68%
“…A prevalent problem in rural areas is the lack of acceptance of digitization of everyday tasks, which is more pronounced than in its urban counterparts [21,22]. In this line, flexible transportation systems, particularly in rural areas, face the challenge of their adoption rate.…”
Section: Adoption Rate In Flexible Transportation Systemsmentioning
confidence: 99%
“…However, there are still obstacles, including technology acceptance (AlDreabi et al, 2023;Ibrahim et al, 2023). Although digital transformation in communications offers many opportunities, not all individuals or communities accept these technologies quickly or have a sufficient understanding of how to use them effectively (Hasebrook et al, 2023;Thanomsing & Sharma, 2024). Inequalities in technology acceptance can strengthen social inequalities, limit participation in the digital economy, and exacerbate population disparities (Dutot, 2014;Ma et al, 2021).…”
Section: Introductionmentioning
confidence: 99%